Analisis Rantai Pasok Ayam Pedaging Pada Peternakan di Desa Kemiri Kecamatan Jenangan Kabupaten Ponorogo - Muhammad Saif Amarullah; Salsa Billa Fauzia; Mochammad Rico Darmansyah; Aloysius Tommy Hendrawan (Jurnal Kendali Teknik dan Sains, 2025)
The farmer's chicken supply chain is a complex system that involves various stages starting from selecting chicken seeds, rearing, feeding, health management, to distribution of the final product to the market. Distribution Channels are closely related to the Supply Chain process, both of which are important in a business, both large and small businesses. The aim of this research is to determine the Broiler Chicken Supply Chain at Kemiri Village Broiler Farms, Jenangan District, Ponorogo Regency. The research method used is observation, interviews and documentation. This broiler farm is under contract with PT. Bintang Tama to supply feed, vitamin medicine, chicken seeds, and also chicken brokers/collectors. Chicken seeds come from PT.Bintang Tama Sentosa after which the chickens are bred for 28 days to 35 days according to the contract with the broker/collector, in 1 harvest/livestock from 3000 seedlings to harvest, the estimated death is 200 deaths, this process cannot be separated from the control carried out by the livestock manager. Chicken farming here is managed well, starting with providing different feeds. Meat chicken seeds are fed with the types of feed, namely pre starter, starter, and finisher, this feed is given at 3 different/not the same age periods for the chickens in 1 harvest. Pak Endra's Farm – Agent – Broiler Chicken Entrepreneur – Market/Restaurant – Final Consumer.